Bioinformatics analysis of inflammation and oncology in pulmonary lymphangioleiomyomatosis. Issue 38 (23rd September 2022) - Su, Wanchun; Zhao, Zimin; Liu, Xin; Xin, Jianfeng; Xia, Song; Shen, Wenbin
Abstract : This study investigates the molecular markers and biological pathways of pulmonary lymphangioleiomyomatosis. We analyzed 2 gene expression profiles in the gene expression omnibus Gene Expression Omnibus database for normal lung tissue and lymphangioleiomyomatosis and identified differential expressed genes in pulmonary lymphangioleiomyomatosis. Ninety-one differentially expressed genes were identified, including 36 upregulated genes and 55 downregulated genes. Hub genes and pathogenic pathways associated with disease development were subsequently identified by enrichment analysis and protein–protein interaction network. Analysis showed that differential expressed genes are mainly involved in the biological behavior of tumor cell proliferation and invasion as well as the inflammatory response. We have identified 10 hub genes in the protein–protein interaction network. Hub genes play an important role in the proliferation and inflammatory response involved in tumor cell proliferation. This study deepens the understanding of lymphangioleiomyomatosis disease and provides a biological basis for further clinical diagnosis and treatment.